Disparities in care by insurance status for individuals with rheumatoid arthritis: analysis of the medical expenditure panel survey, 2006–2009. (1st December 2016) - Cifaldi, Mary; Renaud, Jeanette; Ganguli, Arijit; Halpern, Michael T.
Abstract: Objective: Treatment guidelines for rheumatoid arthritis (RA) recommend early, aggressive treatment with nonbiologic and biologic disease-modifying antirheumatic drugs (DMARDs) to minimize long-term disability. We aimed to assess differences in medical resource utilization, drug therapy, and health outcomes among RA patients by insurance type in the United States. Methods: Individuals with a self-reported diagnosis of RA were identified in the Medical Expenditure Panel Survey (MEPS) database, 2006–2009. Data regarding sociodemographic characteristics, insurance type and status, and outcomes (including health care resource utilization, prescription medication use, health status, and patient-reported barriers to health care) were extracted. Multivariable regression analyses were used to examine the impact of insurance type (private, Medicare, Medicaid, or uninsured) on outcome measures while controlling for age group, sex, and race/ethnicity. Results: A total of 693 individuals with a self-reported diagnosis of RA during the study period were identified; 423 were aged 18–64 years and 270 were aged ≥65 years. Among patients aged 18–64, those with Medicaid or who were uninsured were less likely than those with private insurance to visit a rheumatologist (adjusted odds ratio [aOR] 0.13 and 0.17, respectively; p < .001) and to receive biologic DMARDS (aOR 0.09 [ p < .001] and 0.16 [ p < .01], respectively); those with Medicaid were also less likely to receive nonbiologic DMARDS (aOR 0.26 [ p < .01]). Those with Medicaid were more likely than those with private insurance to be unable/delayed in getting prescription drugs (aOR 2.9 [ p < .05]), to experience cognitive, social, and physical limitations (aOR 8.7 [ p < .001], 4.7 [ p < .001], and 2.5 [ p < .05], respectively); they also reported significantly lower general health and health-related quality of life. Patients aged ≥65 experienced greater equity in care and outcomes. Conclusions: Younger RA patients with Medicaid (including those who receive coverage under the Medicaid expansion component of the Affordable Care Act) may be at risk for inadequate treatment.